Population synchrony in small-world networks - Mike Fowler (Proceedings of the Royal Society B: Biological Sciences, 2008)
Small-world linkage is a revolutionary architecture describing a wide range of social, physical and biological networks. Small-worlds are based on regular network patterns, with some proportion of links replaced by random connections between nodes. We develop this approach for spatially structured populations for the first time, generating novel results across a range of biological models: small-world patterns tend to decrease global synchrony across populations, reducing the risk of global catastrophes. As some element of stochastic dispersal is ubiquitous in natural populations, this work develops a more appropriate paradigm describing dispersal behaviour than purely regular or random linkage patterns.